The Effects of Covid-19 on the Economies of China, EU and US - Doğan, Adem; Öner, Damla (Fırat University, 2022)
The impact of the epidemic on world production and trade began to be felt in the second quarter of 2020. World production and trade contracted in 2020. The Chinese economy felt the impact of epidemic the most in the first quarter of 2020 and the economy contracted seriously. The economy has exhibited its worst growth performance since the introduction of national accounting system in 1992. After the first quarter, Chinese economy recovered rapidly. This recovery is due to exports and industrial production. The EU felt the impact of pandemic the most in the second quarter of 2020. In the second quarter of 2020, the EU countries whose economies contracted the most were Spain, France and Italy, respectively. Ireland is the only EU country whose economy did not shrink this quarter. The effect of the epidemic in US economy was felt most in the second quarter of 2020. GDP contracted compared to the same quarter of the previous year. Job losses in March and April 2020 are more than double the total job losses during the 2008-2009 global financial crisis. US foreign trade has also shrunk significantly.

Salgının dünya üretim ve ticareti üzerine etkisi 2020 yılının ikinci çeyreğiyle birlikte hissedilmeye başlanmıştır. 2020 yılında dünya üretimi ve ticareti daralmıştır. Çin ekonomisi salgının etkisini en çok 2020 yılının birinci çeyreğinde hissetmiştir ve ekonomi ciddi düzeyde daralmıştır. Ekonomi 1992 yılında ulusal muhasebe sistemine başlandığından beri en kötü büyüme performansını sergilemiştir. Birinci çeyrekten sonra Çin ekonomisi hızlı bir şekilde toparlanmıştır. Bu toparlanma ihracat ve sınai üretimden kaynaklanmaktadır. AB pandeminin tesirini en çok 2020 yılının ikinci çeyreğinde hissetmiştir. 2020 yılının ikinci çeyreğinde ekonomileri en fazla daralan AB ülkeleri sırasıyla İspanya, Fransa ve İtalya olmuştur. Bu çeyrekte İrlanda ekonomisi küçülmeyen tek AB ülkesidir. Salgının negatif etkisi ABD ekonomisinde de salgının etkisi en çok 2020 yılının ikinci çeyreğinde hissedilmiştir. GSYİH, önceki yılın aynı çeyreğine kıyasla daralmıştır. 2020 yılının Mart ve Nisan aylarında meydana gelen iş kayıpları 2008-2009 küresel finans krizi dönemindeki toplam iş kaybının iki katından daha fazladır. ABD dış ticareti de ciddi oranda daralmıştır.
COVİD-19’UN ÇİN, AB VE ABD EKONOMİLERİNE ETKİLERİ